Optimized cytogenetic risk-group stratification of KMT2A-rearranged pediatric acute myeloid leukemia - van Weelderen, Romy E; Harrison, Christine J; Klein, Kim; Jiang, Yilin; Abrahamsson, Jonas; Alonzo, Todd; Aplenc, Richard; Arad-Cohen, Nira; Bart-Delabesse, Emmanuelle; Buldini, Barbara; De Moerloose, Barbara; Dworzak, Michael N; et al. (Blood advances, 2024)
A comprehensive international consensus on the cytogenetic risk-group stratification of KMT2A-rearranged (KMT2A-r) pediatric acute myeloid leukemia (AML) is lacking. This retrospective (2005-2016) International Berlin-Frankfurt-Münster Study Group study on 1256 children with KMT2A-r AML aims to validate the prognostic value of established recurring KMT2A fusions and additional cytogenetic aberrations (ACAs) and to define additional, recurring KMT2A fusions and ACAs, evaluating their prognostic relevance. Compared with our previous study, 3 additional, recurring KMT2A-r groups were defined: Xq24/KMT2A::SEPT6, 1p32/KMT2A::EPS15, and 17q12/t(11;17)(q23;q12). Across 13 KMT2A-r groups, 5-year event-free survival probabilities varied significantly (21.8%-76.2%; P < .01). ACAs occurred in 46.8% of 1200 patients with complete karyotypes, correlating with inferior overall survival (56.8% vs 67.9%; P < .01). Multivariable analyses confirmed independent associations of 4q21/KMT2A::AFF1, 6q27/KMT2A::AFDN, 10p12/KMT2A::MLLT10, 10p11.2/KMT2A::ABI1, and 19p13.3/KMT2A::MLLT1 with adverse outcomes, but not those of 1q21/KMT2A::MLLT11 and trisomy 19 with favorable and adverse outcomes, respectively. Newly identified ACAs with independent adverse prognoses were monosomy 10, trisomies 1, 6, 16, and X, add(12p), and del(9q). Among patients with 9p22/KMT2A::MLLT3, the independent association of French-American-British-type M5 with favorable outcomes was confirmed, and those of trisomy 6 and measurable residual disease at end of induction with adverse outcomes were identified. We provide evidence to incorporate 5 adverse-risk KMT2A fusions into the cytogenetic risk-group stratification of KMT2A-r pediatric AML, to revise the favorable-risk classification of 1q21/KMT2A::MLLT11 to intermediate risk, and to refine the risk-stratification of 9p22/KMT2A::MLLT3 AML. Future studies should validate the associations between the newly identified ACAs and outcomes and unravel the underlying biological pathogenesis of KMT2A fusions and ACAs.
Keywords: Myeloid-Lymphoid Leukemia Protein; histonlysin-N-methyltransferasa; Female; Infant; dítě; předškolní dítě; ženské pohlaví; genová přestavba; Adolescent; lidé; prognóza; retrospektivní studie; Histone-Lysine N-Methyltransferase; Male; Chromosome Aberrations; kojenec; chromozomální aberace; Child, Preschool; akutní myeloidní leukemie; Prognosis; Gene Rearrangement; Child; mužské pohlaví; Retrospective Studies; mladiství; Leukemia, Myeloid, Acute; protoonkogenní protein MLL; Humans